PENGARUH PENERAPAN AKUNTANSI TERHADAP PENGEMBANGAN WIRAUSAHA UMKM - Habibie Habibie (JURNAL MUTIARA AKUNTANSI, 2022)
The development of MSMEs is very strategic in driving the national economy, considering that its business activities cover almost all business fields so that the contribution of MSMEs to low-income groups is very large for increasing income. However, the development of MSMEs in Indonesia is very low due to various reasons behind it. Factors that influence the development of MSMEs include the quality of human resources such as the application of accounting in entrepreneurship. The purpose of this study was to determine the effect of accounting application on entrepreneurial development (Empirical Study in Helvetia Tengah Village, Medan). This type of research is causal associative with quantitative techniques with a sample of . The population in this study is MSMEs in the Helvetia Tengah Village area as many as 58 MSMEs and the sample is the total population of 58 respondents. To obtain the data, the research instrument used a Likert scale with four alternative answers in the form of a questionnaire and analyzed using simple linear regression then followed by a t test at and the coefficient of determination at a significant level of 95%.The results of the study indicate that there is an effect of the application of accounting on the development of entrepreneurship.